HIGH LIGHT INDUCED ALTERATIONS IN THE PHOTOSYNTHETIC ELECTRON TRANSPORT ACTIVITIES OF THE WHEAT PRIMARY LEAVES - H. HANUMANTHA REDDY; P. SREE VANI; S. D. S MURTHY (The Bioscan, 2011)
The main source of energy which helps to perform the primary process of photosynthesis is light. In excess, this light in high intensities causes damage to the photosynthetic process. In this investigation an attempt has been made to study the effect of high light (100-430 Wm-2) on photochemical activities of thylakoid membranes isolated from wheat primary leaves. The increase in the intensity of light caused gradual decrease in both whole chain and photosystem (PS) II catalyzed electron transport activities. The PS I catalyzed electron transport gets inhibited by 13% even at high intensities of light. Light intensity measurements clearly demonstrated that the inhibition is more at light saturating conditions than at light limiting conditions. The possible reason for the inhibition of PS II activity at light limiting conditions could be the alterations at light harvesting pigment protein complex in PS II of wheat primary leaves